MIGRATION FACTORS OF BELLES-LETTRES (Scientific journal of the Fergana State University, 2023)
The article analyses the factors of the emergence of plot migration in the world literature, as well as, particularly in national literature on the example of the fable genre. It also discusses examples of creative interactions and artistic connections.